2011
DOI: 10.1128/jcm.00528-11
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Performance Evaluation of the DiversiLab Repetitive-Sequence-Based Genotyping System for Typing Multidrug-Resistant Health Care-Associated Bacterial Pathogens

Abstract: Fast, reliable, and versatile typing tools are essential to differentiate among related bacterial strains for epidemiological investigation and surveillance of health care-associated infection with multidrug-resistant (MDR) pathogens. The DiversiLab (DL) system is a semiautomated repetitive-sequence-based PCR system designed for rapid genotyping. The DL system performance was assessed by comparing its reproducibility, typeability, discriminatory power, and concordance with those of pulsed-field gel electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
(36 reference statements)
2
33
0
2
Order By: Relevance
“…The resulting data are automatically collected, normalised and analysed by the DiversiLab software. A number of studies have evaluated the usefulness of DiversiLab by comparing its performance with current standard typing methods using well-characterised collections of outbreak-related and epidemiologically unrelated bacterial isolates [24][25][26]. These studies have shown that the DiversiLab system is simple, easy to perform, rapid, reproducible, endowed with full typeability and applicable to a wide range of microorganisms.…”
Section: Repetitive-element Polymerase Chain Reactionmentioning
confidence: 99%
“…The resulting data are automatically collected, normalised and analysed by the DiversiLab software. A number of studies have evaluated the usefulness of DiversiLab by comparing its performance with current standard typing methods using well-characterised collections of outbreak-related and epidemiologically unrelated bacterial isolates [24][25][26]. These studies have shown that the DiversiLab system is simple, easy to perform, rapid, reproducible, endowed with full typeability and applicable to a wide range of microorganisms.…”
Section: Repetitive-element Polymerase Chain Reactionmentioning
confidence: 99%
“…Briefl y, genomic DNA extraction and preparation was carried out using the Mo Bio UltraClean™ Microbial DNA Isolation Kit. As previously described, the rep-PCR amplifi cation was performed using the DiversiLab Klebsiella fi ngerprinting kit and detection done using the microfl uidic LabChip kits on Agilent 2100 bioanalyzer according to the manufacturer's instructions (bioMérieux) [14]. The amplifi ed rep-PCR DNA fragment patterns were analyzed with the DiversiLab analysis software using the modifi ed Kullback-Leibler statistical method.…”
Section: Determination Of Clonal Relationshipmentioning
confidence: 99%
“…It may be a suitable alternative to PFGE analysis for epidemic investigation of healthcare-associated pathogens such as methicillin-resistant Staphylococcus aureus, Acinetobacter baumannii, and Klebsiella spp., and has been proven to be a rapid and reliable method for molecular analysis of nosocomial epidemics [26]. Nevertheless, although this method was recently validated for typing of Acinetobacter spp., Escherichia coli, and Klebsiella spp., it was found to be insufficiently discriminative for typing of S. aureus [30,31]. This method can be easily introduced into routine settings and requires less hands-on time than does PFGE.…”
Section: Discussionmentioning
confidence: 99%
“…It should also meet performance criteria, such as full typeability, reproducibility, high discriminatory power, and concordance with validated typing methods as well as consistency with underlying subspecies genetic population structures [30,32,33]. However, such an ideal molecular typing method does not yet exist.…”
Section: Discussionmentioning
confidence: 99%